Stachys milasensis (Lamiaceae), a new species from Turkey - Güner, Özal (Phytotaxa, 2022)
Stachys, among the largest genera of Lamiaceae, includes approximately 370 species (435 taxa) and has a subcosmopolitan distribution. Here, based on their distinctive features of morphological characters, Muğla (Turkey) specimens are determined to represent a distinct species than relevant Stachys species in Turkey and Greece. Stachys milasensis Ö.Güner, described as a new species, belongs to section Swainsoniana and is an endemic species to Turkey. The newly described species shows affinity with S. swainsonii growing in Greece but differs from it in dense villous flowering stems, ovate to oblong-lanceolate cauline leaves, bilabiate calyx and oblong-ovate calyx teeth and oblong-ovate nutlets. In addition to morphological differences, the new species is geographically isolated from S. swainsonii. With this addition, the number of Turkish Stachys species has reached 94 (121 taxa), and 65 (53.7%) of these taxa are endemic.